Potencial de biodegradação de atrazina por bactérias isoladas de solo agrícola - Huergo, Elizabeth Martinez (2024)
The herbicide atrazine is widely used in South America for weed control in various crops, such as corn, sorghum, sugarcane, and landscaping. Its presence as a contaminant in agricultural soils and groundwater and surface waters raises environmental concerns due to its persistence and average lifespan. Although the degradation of atrazine occurs naturally in the soil, both through abiotic and biotic factors, there are still uncertainties about its behavior in relation to local bacterial communities. In this context, this study aimed to evaluate the degradation of atrazine using five bacteria (CCMIBA 1.2; 2; 3; 4, and 5), isolated from agricultural soils with a history of exposure to the herbicide for over 10 years. The isolates are deposited in the Collection of Culturally Important Microorganisms of Biotechnological and Environmental Interest (CCMIBA) at the Federal University for Latin American Integration (UNILA). In the present study, based on the literature, four independent variables were selected, i.e., conditions that could impact the degradation potential, namely: inoculum concentration, atrazine concentration, NH4Cl, and pH. The assays were designed based on a fractional 25-1 experimental design. The assays that showed the best growth were selected for evaluation of phytotoxicity and atrazine degradation: assay 4 (without sucrose, and pH 9) and assay 17 (with sucrose, NH4Cl, and pH 7). The degradation was evaluated by High-Performance Liquid Chromatography (HPLC), revealing a total degradation of 99% in assay 4 and 100% in assay 17. However, phytotoxicity tests with cucumber seeds indicated the maintenance of toxicity, even after degradation, possibly due to the presence of toxic metabolites, suggesting a lack of atrazine mineralization. The results of this study indicate the potential of the studied bacteria to be used in the bioremediation of atrazine and suggest for further studies the optimization of the degradation process, as well as the use of a bacterial consortium as a promising alternative for the complete degradation of this pollutant, reducing its toxicity.